PENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL TIPE GALLERY WALK PADA SISWA KELAS V SDN 59/ II BENIT KECAMATAN RIMBO TENGAH KABUPATEN BUNGO - Yunica Rike Ulfa; Nurlev Avana; Tri Wera Agrita (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research originated from the problem of teachers only focusing on using one model, namely PBL (Problem Based Learning) and also the media used by teachers only using student packets. This resulted in low student learning outcomes. This research is a classroom action research with qualitative and quantitative approaches. The research subjects were 23 fifth grade students of SDN 59/II Benit. This research consists of two cycle. This research was conducted in the even semester of the 2023/2024. This research data was collected through observation, field notes, videos, documentation and test results. The results of the research data analysis show that the use of the Gallery Walk model can improve math learning outcomes in class V. It can be seen in cycle I the completeness of student learning outcomes is 52.18 %, in cycle II student learning outcomes increased to 82.60 %. Thus it can be concluded that learning with the application of the Gallery Walk model can improve student learning outcomes in grade V mathematics learning at SDN 59/II Benit.